Shigella serogroups identified from adult diarrhoeal out-patients in Addis Ababa, Ethiopia: antibiotic resistance and plasmid profile analysis. - Mache, A; Mengistu, Y; Cowley, S (1997)
Fifty shigella strains were isolated from 700 diarrhoeal samples collected from adult diarrhoeal out-patients in Addis Ababa. Among the isolates, serogroup A comprised 28%, B 44%, C 18% and D 10%. Among all shigella serogroups, highest resistance was encountered to tetracycline (74%), ampicillin (70%), cephalothin (64%), trimethoprim-sulfamethoxazole (52%) and chloramphenicol (50%) while least resistance was observed to gentamicin (0%), polymyxin B (10%) and nalidixic acid (14%). Gentamicin, polymyxin B and nalidixic acid were found to be the drugs of choice for cases of shigellosis. All drug resistant isolates analysed for plasmids contained multiple plasmids ranging from 1.8 to greater than 21 Kilobases.